PERAN PENDIDIK DALAM MENGHADAPI KERAGAMAN GAYA BELAJAR MURID - Hendrick Sine (Sekolah Tinggi Alkitab Tiranus, 2019)
An understanding on student learning style is very important for educators. It aims to build an effective and creative learning in responding students’ unique styles of learning. In addition, the design of teaching materials and utilization of methods should be relevant to the needs of learners. However, the reality is that the understanding is still not maximal. Therefore, competence and role of educator is required in preparing it, so that the process of learning in class becoming meaningful, inspiring, enlightening, creative, transformative and productive. The research method used in this writing is qualitative method. The results of this study conclude that if the educator is lack of understanding about children's learning styles and their own learning styles, can cause learning process that is not effective and creative. Whereas the educators who understand the differences in learning styles will be able to create an effective, creative and productive learning process.